Creative, Innovative and Effective Teacher Training in Islamic Boarding School - Muhammad Hajarul Aswad; Fadhliyah Rahmah Muin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Teachers are increasingly required to present learning material that is more creative, innovative and effective in presenting learning in class, included the English Teacher and Math Teacher. Therefore, the purpose of this training is to provide training to English and Math teachers on how to develop creative, innovative and active learning in learning. In addition, giving experience to the teacher on how to develop creative learning media in the classroom as well as knowing how the ability of teachers of after participating in the Teacher Training program. This is a Community service method with research based. The method used is Asset Based Community-driven Development. All participants were provided with 9 units of material in this teacher training. After attending this teacher training, learning in class is more interesting and enjoyable because the English and Math teachers present learning material that is creative, innovative and effective.